Comparison of Corneal Collagen Cross-Linking and Voriconazole Treatments in Experimental Fungal Keratitis for Aspergillus fumigatus - Zhao, Zhennan; Chen, Xueli; Shao, Yi; Shao, Tingting (Frontiers in Medicine, 2022)
Aims: To compare the antifungal efficacy of corneal cross-linking（CXL）and voriconazole in experimental aspergillus keratitis models. Methods: Thirty-nine New Zealand rabbits were divided into three groups: a control group, a voriconazole group (M group), and a voriconazole combined with CXL group (CXL-M group). The ulcer area was measured via slit lamp imaging, the corneal and corneal epithelial thickness, and ulcer depth was measured via anterior segment optical coherence tomography (AS-OCT). The existence time of the hyphae was observed via in vivo confocal microscopy (IVCM), and the cornea was taken for pathological examination after modeling and at the end of the study to determine the hyphae and corneal repair. The observation times were as follows: at successful modeling and at 1, 4, 7, 14, 21, and 28 days after intervention. Results: In the CXL-M group, ulcer area and depth decreased continuously from Day 4 to Day 28 after CXL (all P< 0.05). In the CXL-M group, ulcer area and depth were smaller than those in the other two groups from Day 4 to Day 21 after CXL (all P< 0.05, except ulcer area in the CXL-M vs M group on Day 21). The duration of hyphae in the CXL-M group was significantly shorter than in the other two groups (P = 0.025). On Day 28, in CXL-M group, corneal thickness was thicker than baseline (P < 0.05). Meanwhile, in CXL-M group, corneal and corneal epithelial thickness were significantly thinner than in the other two groups (P < 0.001). The CXL-M group had no complications, such as corneal perforation, at the end of the study. Conclusions: Voriconazole combined with CXL is effective in treating aspergillus-infected keratitis. Combined therapy could effectively inhibit aspergillus, accelerate corneal repair, and shorten the course of the disease.